2005
DOI: 10.1103/physrevb.72.035344
|View full text |Cite
|
Sign up to set email alerts
|

Spin gap in the two-dimensional electron system ofGaAsAlxGa1xAssi

Abstract: We study the interaction-enhanced spin gaps in the two-dimensional electron gas confined in GaAs/AlGaAs single heterojunctions subjected to weak magnetic fields. The values are obtained from the chemical potential jumps measured by magnetocapacitance. The gap increase with parallel magnetic field indicates that the lowest-lying charged excitations are accompanied with a single spin flip at the odd-integer filling factor ν = 1 and ν = 3, in disagreement with the concept of skyrmions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…The linear dependence of ǻ on B is qualitatively different from what is expected for QHF, which predicts 21 a gap that scales as B 1/2 . It is worth noting, however, that early studies 36,37 of the exchange-enhanced spin gap at Ȟ = 1 in GaAs samples also showed an energy gap that was linear in B. QHF predicts 21 ǻ ~ 100 meV for magnetic fields of a few Tesla, far larger than we observe, but this discrepancy is likely due to disorder in our samples.…”
contrasting
confidence: 77%
“…The linear dependence of ǻ on B is qualitatively different from what is expected for QHF, which predicts 21 a gap that scales as B 1/2 . It is worth noting, however, that early studies 36,37 of the exchange-enhanced spin gap at Ȟ = 1 in GaAs samples also showed an energy gap that was linear in B. QHF predicts 21 ǻ ~ 100 meV for magnetic fields of a few Tesla, far larger than we observe, but this discrepancy is likely due to disorder in our samples.…”
contrasting
confidence: 77%
“…26 However, the skyrmion at ν = 3 is fragile and it was found that Landau-level mixing tends to favor spinpolarized quasiparticles. 27 It was indicated that the lowestlying charged excitations at ν = 3 was accompanied with a single spin flip at B 2 T. 28 Depolarization of the degree of circular polarization of the PL P = (I σ − − I σ + )/(I σ − + I σ + ) is expected at ν > 3 and at ν < 3 for the skyrmion ground state. The PL intensities at around ν = 3 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The exchange energy of a single spin-flip excitation is supposed to be responsible for a serious enhancement of the excitation energy in comparison to the single-particle Zeeman splitting [2][3][4][5] . This enhancement is sensitive 2 to the excitation wave vector k. It is widely accepted, that in transport experiments 3,4,6,7 k = ∞ excitations are tested, while optical investigations 5 allow to probe excitations at different k. In low magnetic fields, the possibility of complicated spin textures (skyrmions) formation is still debated 6,7 .…”
mentioning
confidence: 99%